Bergson and the spiritualist origins of the ideology of creativity in philosophy - Bianco, Giuseppe (Taylor & Francis, 2020)
Henri Bergson (1859–1940), the most prominent member of nineteenth-century French spiritualism, is the first philosopher who explicitly defined philosophy as a practice which consists in posing problems anew and in creating concepts. In this article, I will try to reconstruct the progressive importance acquired by the terms ‘problem’ and ‘concept’ in nineteenth-century French philosophy and how they combined in Bergson’s theories about creativity, invention and novelty. I will argue that Bergson’s conception of philosophy as a creative intellectual practice was the result of a negotiation, inside a pre-existent spiritualist framework, between, on the one hand, neo-Kantianism and, on the other hand, evolutionism which strongly influenced empirical psychology and the emerging social sciences. Bergson’s solution, influenced by the evolution of mathematics and literary theory, was just one of the possible options, and the main alternative to a new form of transcendental philosophy.
Keywords: Bergson; creation; interiority; lexicography; Spiritualism